PEMANFAATAN BUAH PEDADA DAN BUAH API-API PADA PEMBUATAN FRUIT LEATHER - Wulandari, Ayu Sri; Hamzah, Farida Hanum; Herawati, Netti (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
The purpose of this research was to get the best combination of pedadaporridge and api-api porridge. The research used a Complete Randomized Design (CRD) with 5 treatments and 3 replications.The treatments were PA1 (Pedadaporridge 90% :api-api porridge10%), PA2 (Pedadaporridge 80% : api-api porridge 20%), PA3 (Pedadaporridge 70% : api-api porridge30%), PA4 (Pedadaporridge 60% : api-api porridge40%) and PA5 (Pedadaporridge 50% : api-api porridge 50%). The data obtained were analyzed statistically using Anova and DNMRT at 5%. The research showed that usingpedadaporridgeand api-api porridge water content, ash content, degree of acidity (pH), protein content, fat content, reduction sugar content, crude fiber content and organoleptic test. The best treatment of fruit leather from this research is PA3 whichwater content 9,19%, ash content 1,05%, degree of acidity (pH) 3,13, protein content 1,87%, fat content 0,28%, reduction sugar content 43,17% and crude fibercontent 4,62%. Rather green colour, a little bit pedadaporridgeand api-api porridgeflavour, sour taste slightly sweet, the texture rather springy and overall assesment of fruit leather was preferred by the panelist. Keywords :Fruit leather, pedadaporridge and api-api porridge.